2003
DOI: 10.1016/s0896-6273(03)00594-4
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Axonal Transport by Loss of Huntingtin or Expression of Pathogenic PolyQ Proteins in Drosophila

Abstract: We tested whether proteins implicated in Huntington's and other polyglutamine (polyQ) expansion diseases can cause axonal transport defects. Reduction of Drosophila huntingtin and expression of proteins containing pathogenic polyQ repeats disrupt axonal transport. Pathogenic polyQ proteins accumulate in axonal and nuclear inclusions, titrate soluble motor proteins, and cause neuronal apoptosis and organismal death. Expression of a cytoplasmic polyQ repeat protein causes adult retinal degeneration, axonal block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
477
2
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 587 publications
(512 citation statements)
references
References 50 publications
28
477
2
5
Order By: Relevance
“…Consistent with our hypothesis that Htt-Q128 expression causes neurodegeneration secondary to impairment of axonal transport, recent studies have found that neurodegeneration is a primary consequence of axonal transport defects in non-polyQ diseases as well, including Alzheimer's disease (26)(27)(28). During review of our manuscript, two reports have been published that document similar axonal transport defects in HD models (29,30). Determining the precise mechanisms by which Htt aggregates physically attach to the axonal cytoskeleton will likely provide important insights into the mechanisms of axonal transport blockage in HD.…”
Section: Resultssupporting
confidence: 87%
“…Consistent with our hypothesis that Htt-Q128 expression causes neurodegeneration secondary to impairment of axonal transport, recent studies have found that neurodegeneration is a primary consequence of axonal transport defects in non-polyQ diseases as well, including Alzheimer's disease (26)(27)(28). During review of our manuscript, two reports have been published that document similar axonal transport defects in HD models (29,30). Determining the precise mechanisms by which Htt aggregates physically attach to the axonal cytoskeleton will likely provide important insights into the mechanisms of axonal transport blockage in HD.…”
Section: Resultssupporting
confidence: 87%
“…One strong possibility is axonal transport. Disruption of axonal transport can lead to neuronal cell death in mice (LaMonte et al, 2002) and Drosophila (Gunawardena and Goldstein, 2001;Gunawardena et al, 2003). Although the underlying mechanism connecting microtubule dynamics to axonal transport is unclear, low concentrations of taxol have been shown to compromise axonal transport (Nakata and Hirokawa, 2003).…”
Section: How Might Tau Dysfunction Cause Neurodegeneration?mentioning
confidence: 99%
“…Polyglutamine expansion in mutant Htt causes Huntington's disease, a neurodegenerative disorder that primarily affects striatal neurons. Mutant Htt disrupts axonal transport in squid axoplasm (7), Drosophila (8), and mammals (9,10), suggesting a role for the protein in vesicle transport. Htt interacts with various proteins implicated in trafficking (6,11), including Htt-associated protein-1 (HAP1), which in turn interacts with both dynactin and kinesin (12)(13)(14).…”
mentioning
confidence: 99%